Acupuncture Care for Adiposity Patients at "T'ADE" Cilegon Health Clinic - Fatimatuzzahro Fatimatuzzahro; Puspo Wardoyo; Ikhwan Abdullah; Chantika Mahadini (Jurnal Indonesia Sosial Sains, 2026)
Adiposity is a chronic metabolic disorder characterized by excessive fat accumulation and an increased risk of noncommunicable diseases. Its rising prevalence in Indonesia requires effective and safe therapeutic approaches. Acupuncture, as a complementary therapy, is considered to have potential in regulating metabolism and energy balance. This study aims to determine the effectiveness of acupuncture treatment for weight loss in adiposity patients at the Sehat “Tade” Clinic, Cilegon. The study used a qualitative approach with a case study method involving one 48-year-old female participant with a BMI of 37 kg/m². Acupuncture therapy was performed in six sessions over three weeks. Data were obtained through the four Traditional Chinese Medicine (TCM) examination methods: observation (Wang), listening and smelling (Wen), inquiry (Wen), and palpation (Qie). Effectiveness was assessed based on a comparison of pre- and post-intervention conditions, including weight loss, changes in BMI, clinical complaints, and TCM examination results. After six therapy sessions, there was weight loss and improvement in clinical complaints such as low back pain and headache. TCM examination showed improvement in tongue condition, reduced abdominal tenderness on palpation, and enhanced energy levels and emotional regulation in the patient. The participant also demonstrated positive changes in diet, rest, and physical activity. Acupuncture treatment administered in a structured and individualized manner is effective in promoting weight loss and improving clinical conditions in adiposity patients. This therapy has the potential to serve as a complementary approach in adiposity management and can be further developed through studies with a larger number of participants.